Long-term seizure outcome with the surgically remediable syndrome of frontal lobe epilepsy associated with superior frontal sulcus-related dysplasia - Xu, Yan; Hu, Wen-Han; Shao, Xiao-Qiu; Ma, Yan-Shan; Lou, Lin; Zhang, Kai; Zhang, Jian-Guo (Frontiers in Neurology, 2023)
Objective To assess the long-term outcome of the surgically remediable syndrome of frontal lobe epilepsy (FLE) associated with superior frontal sulcus (SFS)-related dysplasia. Methods We retrospectively reviewed the medical charts and surgical features of 31 patients with drug-resistant frontal lobe epilepsy in our centers between 2016 and 2018. All patients underwent surgical resection. According to the epileptogenic zone (EZ), localization and resection extent were classified as (1) pure SFS group (PS group), (2) associated SFS group (AS group), and (3) no SFS group (NS group). The general characteristics, neuroradiological findings, morbidity, pathology, and long-term seizure outcome after surgery were analyzed to extract the potential value of the surgery for SFS-related dysplasia. Results Of 31 patients with FLE who underwent epilepsy surgery, 15 patients (nine men) were included PS group, five patients (five men) in the AS group, and 11 patients (eight men) in the NS group. Eleven patients detected abnormal focal signals in the presurgical MRI. Six patients in the PS group demonstrated the suspected focal cortical dysplasia (FCD) in the SFS detected with MRI. All patients demonstrated focal abnormal hypometabolism foci in the PET-MR co-registration. Twenty-five patients (80.6%) were seizure-free since surgery, including all 15 patients (100%) of the PS group, three in five patients (60%) of the AS group, and seven in 11 patients (63.6%) of the NS group. The difference in outcome between different groups was significant (p = 0.004, PS vs. AS group; p = 0.005, PS vs. NS group). As of the last follow-up (mean 66.2 ± 9.7months), 25 patients (80.6%) were seizure-free since surgery (Engel's class I). In addition, antiseizure medication was withdrawn in 19 patients (61.3%). Histologic examination of resected specimens revealed FCD in all 31 patients. The percentage of FCD II type was 100, 60, and 63.6% in the three different groups, respectively. Conclusion SFS-related dysplasia is a neuropathologic entity with a favorable postoperative outcome. FCD II is the most common type of SFS-related dysplasia. FDG-PET co-registered with MRI should be performed in patients with suspected SFS-related dysplasia, since it may depict areas of hypometabolism suggestive of dysplasia in the absence of MRI abnormalities.